Use of all-male triploid population of zebrafish (Danio rerio) for evaluation of 17α-ethinylestradiol effects - Weiserova, Zuzana; Zentrichova, Viola; Medkova, Denisa; Blahova, Jana; Franc, Ales; Garajova, Michaela; Mares, Jan; Postulkova, Eva; Franek, Roman; Psenicka, Martin; Marsalek, Petr; Svobodova, Zdenka (Neuro-endocrinology letters, 2022)
OBJECTIVES: We tested the toxicity of ethinylestradiol, a semisynthetic estrogen used in oral contraceptives, on all-male triploid zebrafish using commercial feeds and three different doses concentrations. We aimed to determine whether ethinylestradiol peroral administration resulted in vitellogenin production and whether all-male triploid zebrafish could serve as a model species for xenoestrogen testing. METHODS: The actual concentrations of 17α-ethinylestradiol were 0.0035 (low); 0.0315 (medium) and 0.365 (high) μg/g. Positive control represented commercial feeds containing 0.0465 μg/g of β-estradiol. The experiment lasted 8 weeks. RESULTS: Our results indicate that 17α-ethinylestradiol consumption does induce vitellogenin production in triploid zebrafish. CONCLUSIONS: The simple presence of vitellogenin is a definite symptom indicative of the potential for such changes due to the action of estrogenic substances. As such, this experiment has shown that the use of all-male triploid zebrafish populations, rather than the mixed-sex populations of other species previously used, could serve as a suitable alternative model population for controlled testing of the effects of xenoestrogens on fish.
Keywords: Triploidy; dánio pruhované; Animals; Zebrafish; vitelogeniny; estrogeny; triploidie; mužské pohlaví; zvířata; Estrogens; Male; Ethinyl Estradiol; chemické látky znečišťující vodu; Vitellogenins; ethinylestradiol; Water Pollutants, Chemical